Invasive rhinocerebral mucormycosis with orbital extension in poorly- controlled diabetes mellitus - Hasmoni, Mohamed Hadzri; Mohd Shah, Azarisman Shah; Abdul Rani, Mohammed Fauzi; Abdullah, Kahairi (Singapore Medical Association, 2009)
Rhinocerebral mucormycosis is an invasive fungal sinusitis with a high mortality rate, especially in immunocompromised patients. A 70-year-old woman, with uncontrolled type 2 diabetes mellitus, presented with a one-month history of non-specific headaches associated with progressive swelling of her left eye. Computed tomography of the brain and orbits showed the extensive involvement of bilateral intranasal sinuses, orbits, extraocular muscle and soft tissues. The diagnosis of invasive mucormycosis was confirmed from a tissue biopsy taken from the internasal septum. Despite the extensive mucormycosis invasion, she was successfully treated with intranasal and systemic amphotericin B and minimal adjunctive intranasal sphenoidotomy.